The habit sucking thumb as the etiology factor of malocclusion: literature review: Kebiasaan mengisap ibu jari sebagai faktor etiologi maloklusi - Eddy Heriyanto Habar; Aldi Said; Eka Erwansyah (Makassar Dental Journal, 2021)
Background: Sucking thumb is a bad oral habit that may cause a dentofasial alteration that affects the process of swallowing, mastication, breathing, phonetic, densupporting structure, esthetic, and also the teeth occlusion. Objective: To show the habit of sucking thumb is the etiology factor of malocclusion. Method: Literature review was conducted by collecting various information regarding the topic and perform the synthesis. Result: From 8 scientific research, it was known that the habit of suck-ing thumbs is one of the etiology factors of malocclusion. The most common type of malocclusion found on individuals were anterior openbite, followed by Class II occlusion, increased in overjet, and crossbite posterior. Conclusion: The habit of suck-ing thumb may cause malocclusion; so that a preventive action must be taken to eliminate the habit during the development and growth stage.